The Effects of Different Age Categories on Overall Survival in Adults Patients Undergone Liver Transplantation - Akbulut, Sami; Yilmaz, Mehmet; Karabulut, Koray; Ara, Cengiz; Yilmaz, Sezai (Wiley-Blackwell, 2012)
[Abstract Not Available]
18th Annual International Congress on ILTS -- MAY 16-19, 2012 -- San Francisco, CA